Analisis Perancangan Sistem Informasi Akuntansi Penjualan dan Penerimaan Kas Pada Perusahaan - Noerlina, Noerlina; Karmawan, I Gusti Made; Rahadi, Nosyar (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The objective of writing this paper is to find weaknesses in a sales information system and company income cash; and also to try to suggest a new system design so it could increase the information quality and help reducing existed problems. The method used is data collecting, analysis, and designing method by using data flow diagram, structured diagram, flow chart, and entity relationship diagram. The expected result is the better information quality and easiness in searching transactions. Therefore it could be concluded that by increasing information quality, the decision making quality could also be increased. Besides, system could ease management in searching sales and cash income information.